ANALISIS PENGALAMAN PENGGUNA PADA FITUR SHOPEE FOOD MENGGUNAKAN METODE HEURISTIC EVALUATION - Triana, Ananda; Afifah, Afifah; Pontoh, Zaenab (JTRISTE, 2024)
This research focuses on user experience through the Shopee Food feature, the aim is to determine the extent of the user experience of the Shopee Food feature service in several categories, namely gender, age and profession. In this research, the method used by the author is the heuristic evaluation method which consists of 10 aspect stages, which will be calculated based on the severity ratings formula for assessing. So the results obtained are: 10 aspects of this heuristic evaluation method, namely the first aspect: Visibility of System Status with a value of 7.863%, the second aspect: Match between the System and the Real World with a value of 8.063% , third aspect: User control and freedom with a value of 8.400%, fourth aspect consistency and standards with a value of 11.813%, fifth aspect: Error prevention with a value of 7.338%, sixth aspect: Understanding rather than warning (Recognition rather than recall) with a value of 7.413%, seventh aspect: Flexibility and efficiency of use (Flexibility and efficiency of use) with a value of 7.925%, eighth aspect: Aesthetic and minimalist design (Aesthetic and Minimalist Design) with a value of 6.275%, ninth aspect: Help users, recognize, diagnose and recover from awareness (Help user recognize, diagnose and recover from errors) with a value of 7.675%, tenth aspect: Help and documentation (Help and documentation) with a value of 8.063%.